MEKANISME PEMBIAYAAN KPR GRIYA AGENG PURWOSARI DENGAN AKAD AL-ISTISHNA’ PADA PT. BPRS KOTA MOJOKERTO KANTOR CABANG PANDAAN KABUPATEN PASURUAN - Abdillah Mundir (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Every human being certainly wants a decent life, needs can be fulfilled, not only food and clothing are needed but also a house. The problem of housing needs, of course, will not be an individual problem. But it is also a problem that must be faced jointly by the government and its people. Because if more and more people are homeless, of course, it will add to the slum areas in this country. To overcome these problems, the government through banking institutions helps the people, especially the weak economic groups, to get houses. As with the creation of a KPR Financing product (House Ownership Credit) with ancontract Istishna' at the Mojokerto City BPRS, Pandaan Branch, Pasuruan Regency, the purpose of this thesis research is to determine the mechanism for financing Griya Ageng Purwosari's mortgage with ancontract Al-Istishna' as well as the benefits and types of risks. faced by the Mojokerto City BPRS. The method used in this research is descriptive qualitative method. The study used data collection techniques of observation, interviews and documentation. Based on the results of the study, it can be concluded that the Griya Ageng Purwosari mortgage financing mechanism with thecontract Al-Istishna' is in accordance with sharia where the Bank requires the developer/developer and the customer to order and determine the specifications of the desired house. This financing also has several benefits and risks that are adjusted to the source of the risk, because infinancing Al-Istishna' there are 3 parties involved, namely the customer, the bank, and the developer. From these benefits and risks, the Mojokerto City BPRS has been able to minimize the impact of the risk of financing the Griya Ageng Purwosari mortgage with thecontract Al-Istishna'.